2021
DOI: 10.1037/ort0000531
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness, mental health, and social health indicators in LGBTQIA+ Australians.

Abstract: Loneliness is a growing public health concern that is associated with poor mental health (e.g., social anxiety, depression) and increased physical health problems (e.g., cardiovascular disease, sleep disturbances). Socially vulnerable groups such as the elderly, migrants, and asylum seekers are more susceptible to the effects of loneliness. We examined loneliness severity in lesbian, gay, bisexual, transgender, queer, intersex, asexual, and other sexual orientation and gender identity diverse (LGBTQIAϩ) commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 56 publications
(85 reference statements)
4
39
2
Order By: Relevance
“…However, it may damage the victims’ psychological well-being in several ways. Firstly, sexual orientation microaggression may make LGB individuals feel misunderstood by (and different from) others, and the feeling of loneliness may deteriorate LGB individuals’ mental health [ 42 ]. Secondly, enactors of microaggression might view their own behavior as harmless, unremarkable, or well-intentioned [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it may damage the victims’ psychological well-being in several ways. Firstly, sexual orientation microaggression may make LGB individuals feel misunderstood by (and different from) others, and the feeling of loneliness may deteriorate LGB individuals’ mental health [ 42 ]. Secondly, enactors of microaggression might view their own behavior as harmless, unremarkable, or well-intentioned [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Eres et al [ 38 ] associated loneliness with mental health and physical wellbeing in the LGBTQI+ population. Added to this, socially vulnerable groups, such as the elderly, migrants, and asylum seekers, are more susceptible to the effects of loneliness.…”
Section: Resultsmentioning
confidence: 99%
“…Research in Australia examined loneliness severity in lesbian, gay, bisexual, transgender, queer, intersex, asexual, and other sexual orientation and gender identity diverse (LGBTQIA+) communities. They found that LGBTQIA+ adults had higher levels of loneliness than non- LGBTQIA+ adults [ 45 ]. Sanchez et al [ 46 ] examined ED utilization in a sample of 360 lesbian, gay, and bisexual individuals and found that over the previous 12 months, 25.3% had at least one ED visit and 16% had two or more visits.…”
Section: Discussionmentioning
confidence: 99%